Dynamics of Gastrointestinal Activity and Ruminal Absorption of the Methane-Inhibitor, Nitroethane, in Cattle - Božic, Aleksandar K.; Gutiérrez-Bañuelos, Hector; Corral-Luna, Agustin; Carstens, Gordon; Arévalos-Sánchez, Martha María; Félix-Portillo, Monserrath; Muro-Reyes, Alberto; Arzola-Álvarez, Claudio; Anderson, Robin C.; Harvey, Roger B. (Frontiers in Veterinary Science, 2022)
Nitroethane is a potent methane-inhibitor for ruminants but little is known regarding simultaneous effects of repeated administration on pre- and post-gastric methane-producing activity and potential absorption and systemic accumulation of nitroethane in ruminants. Intraruminal administration of 120 mg nitroethane/kg body weight per day to Holstein cows (n = 2) over a 4-day period transiently reduced (P < 0.05) methane-producing activity of rumen fluid as much as 3.6-fold while concomitantly increasing (P < 0.05) methane-producing activity of feces by as much as 8.8-fold when compared to pre-treatment measurements. These observations suggest a bacteriostatic effect of nitroethane on ruminal methanogen populations resulting in increased passage of viable methanogens to the lower bovine gut. Ruminal VFA concentrations were also transiently affected by nitroethane administration (P < 0.05) reflecting adaptive changes in the rumen microbial populations. Mean (± SD) nitroethane concentrations in plasma of feedlot steers (n = 6/treatment) administered 80 or 160 mg nitroethane/kg body weight per day over a 7-day period were 0.12 ± 0.1 and 0.41 ± 0.1 μmol/mL 8 h after the initial administration indicating rapid absorption of nitroethane, with concentrations peaking 1 day after initiation of the 80 or 160 mg nitroethane/kg body weight per day treatments (0.38 ± 0.1 and 1.14 ± 0.1 μmol/mL, respectively). Plasma nitroethane concentrations declined thereafter to 0.25 ± 0.1 and 0.78 ± 0.3 and to 0.18 ± 0.1 and 0.44 ± 0.3 μmol/mL on days 2 and 7 for the 80 or 160 mg nitroethane/kg body weight per day treatment groups, respectively, indicating decreased absorption due to increased ruminal nitroethane degradation or to more rapid excretion of the compound.